Peningkatan Hasil Belajar Kurikulum Merdeka Dengan Menggunakan Metode Pembelajaran Role Play Berbantuan Media Gambar dan Proyektor Kelas II UPTD SDN 145 Inpres Pampangan - Haslinda Haslinda; Sri Rezky Wahyuni; Widia Ayu Lestari (Pusat Riset dan Inovasi Nasional, 2023)
This research aims to improve the learning outcomes of the independent curriculum by using the role play learning method assisted by image media and a projector in class II UPTD SDN 145 Inpres Pampangan. This research is Classroom Action Research, the subjects of this research are class 2, totaling 32 students consisting of 20 boys and 12 girls. This research was carried out for 3 weeks. The implementation of this action was carried out in 2 cycles, the first cycle consisting of 3 meetings and the second cycle consisting of 3 meetings. This research was carried out in the Teaching Profession Strengthening (P2K) activities which started on September 4 - October 14 in the 2023/2024 academic year. The results of the research show that during the learning process there is a change in students' attitudes during the learning process in accordance with the results of observations, namely the implementation of the Role Play type cooperative learning model assisted by picture media and projectors can increase students' self-confidence in asking both the teacher and their friends about the material. that are not understood and can improve student attendance. So, Role Play cooperative learning assisted by image media in thematic learning is suitable for use in this class. This can be seen from the increase in learning outcomes for class II students at UPTD SDN 145 Inpres Pampangan after the Role Play type of cooperative learning was held with the help of image media and a projector.